y,z=var('y,z'); solve(6*x + 10*y + 15*z ==1,x,y,z) gives
([{x: -5/3*y - 5/2*z + 1/6}], [1])

while
solve(x+y==3,x,y) gives
([x == -y + 3], [1])

My questions are:
1) Why the notation are different in the 2 and 3-variable case? One
gives x: and the other x==

2) What the [1] in both cases stand for ?

3) In order to get the parameters appear in the solution, one need to
add a redundant equation. Shall we improve on that?
e.g.
solve([x+y==3,2*x+2*y==6],x,y)
[[x == -r1 + 3, y == r1]]

-- 
To post to this group, send an email to sage-devel@googlegroups.com
To unsubscribe from this group, send an email to 
sage-devel+unsubscr...@googlegroups.com
For more options, visit this group at http://groups.google.com/group/sage-devel
URL: http://www.sagemath.org

Reply via email to